Exposure to environmental contaminants is associated with altered hepatic lipid metabolism in non-alcoholic fatty liver disease - Sen, Partho; Qadri, Sami; Luukkonen, Panu K.; Ragnarsdottir, Oddny; McGlinchey, Aidan; Jäntti, Sirkku; Juuti, Anne; Arola, Johanna; Schlezinger, Jennifer J.; Webster, Thomas F.; Orešič, Matej; Yki-Järvinen, Hannele; et al. (Journal of hepatology, 2022)
Recent experimental models and epidemiological studies suggest that specific environmental contaminants (ECs) contribute to the initiation and pathology of non-alcoholic fatty liver disease (NAFLD). However, the underlying mechanisms linking EC exposure with NAFLD remain poorly understood and there is no data on their impact on the human liver metabolome. Herein, we hypothesized that exposure to ECs, particularly perfluorinated alkyl substances (PFAS), impacts liver metabolism, specifically bile acid metabolism. In a well-characterized human NAFLD cohort of 105 individuals, we investigated the effects of EC exposure on liver metabolism. We characterized the liver (via biopsy) and circulating metabolomes using 4 mass spectrometry-based analytical platforms, and measured PFAS and other ECs in serum. We subsequently compared these results with an exposure study in a PPARa-humanized mouse model. PFAS exposure appears associated with perturbation of key hepatic metabolic pathways previously found altered in NAFLD, particularly those related to bile acid and lipid metabolism. We identified stronger associations between the liver metabolome, chemical exposure and NAFLD-associated clinical variables (liver fat content, HOMA-IR), in females than males. Specifically, we observed PFAS-associated upregulation of bile acids, triacylglycerols and ceramides, and association between chemical exposure and dysregulated glucose metabolism in females. The murine exposure study further corroborated our findings, vis-à-vis a sex-specific association between PFAS exposure and NAFLD-associated lipid changes. Females may be more sensitive to the harmful impacts of PFAS. Lipid-related changes subsequent to PFAS exposure may be secondary to the interplay between PFAS and bile acid metabolism. There is increasing evidence that specific environmental contaminants, such as perfluorinated alkyl substances (PFAS), contribute to the progression of non-alcoholic fatty liver disease (NAFLD). However, it is poorly understood how these chemicals impact human liver metabolism. Here we show that human exposure to PFAS impacts metabolic processes associated with NAFLD, and that the effect is different in females and males. [Display omitted] •Environmental contaminants may contribute to the initiation and development of NAFLD.•Exposure to PFAS is associated with the alteration of bile acid profiles and NAFLD-related pathways in the human liver.•Other lipid-related changes may be secondary to the interplay between PFAS and bile acid metabolism.•Females may be more sensitive to the harmful impacts of PFAS than males.